On the Nature of Some Features of Sensory and Perceptual Spheres in Autism Spectrum Disorders - S.A. Morozov; T.I. Morozova (Moscow State University of Psychology and Education, 2020)
The purpose of present article is the analysis of the existing views to features of the sensory and perceptual spheres in autism, and to nature and mechanisms of development of these spheres. Main existing hypotheses are considered (the Weakness of Central Coherence Phenomenon and the Phenomenon of Enhances Perceptual Functioning), unresolved aspects of a problem are marked out. Particular attention is paid to the variability of not only the thresholds of perception and discomfort, but also the differential sensitivity. The high level of differential sensitivity connected to the ability to distinguish unusually short time intervals which is considered as the core mechanism of the analyzed hypotheses, significantly influencing perception of time in autism and, in particular, mnemonic processes. The possible consequences for development of some kinds of stereotypies and other symptoms of autism, the possible directions and prospects of further investigations are discussed.